Hemodynamic management of the preterm infant with acute respiratory failure: role of the functional echocardiography - Mannarino, S.; Corona, G.; Zaroli, A.; Codazzi, A. C.; Pasotti, M.; Cerbo, R. M.; Stronati, M. (Acta Biomedica Atenei Parmensis, 2015)
The functional echocardiography is a useful tool to evaluate the hemodynamic status of preterm infants, often needing a respiratory support during the first critical days of life. In NICU it can be helpful either for the clinical monitoring or the therapeutic management and the use of this technique can potentially improve short-term outcome of preterm infants.